(untitled) (Research, Society and Development, 2021)
Aim: The present study aimed to assess the level of knowledge and applicability of the ICF in physiotherapy professionals. Methods: This is an exploratory, descriptive cross-sectional study with a quantitative approach, involving physiotherapists who live in Pernambuco and are active in CREFFITO-1. The volunteers answered a questionnaire about the CIF developed by the researchers through the Google Forms platform. The collected data were tabulated by means of a spreadsheet, and this was presented descriptively and, later, having their results compared through tests considering the security level <0.05 by the software Statistical Package for the Social Sciences (SPSS), version 22.0. Results: The sample of the present study consisted of 55 physical therapists, with a predominance of females and professionals in the field of trauma orthopedics (34.4%) and neurology (23.3%). Among the participants, 94.5% claimed to know the ICF, but only 28.8% of the professionals apply this classification in their work environment, as a tool for assessing and evolving the patient during conduct. Conclusion: It is concluded that, although the physiotherapists know the ICF, many do not use it in their clinical practice and, of the participants who use it, only apply it when they really feel prepared for its use.